Host Plant Species Of The New Invasive Pest, Fall Armyworm (Spodoptera Frugiperda) In South Sumatra. Issue 1 (1st April 2022) - Herlinda, S; Simbolon, I M P; Hasbi,; Suwandi, S; Suparman,
Abstract: The new invasive pest, fall armyworm (Spodoptera frugiperda) has been found in West Sumatra since March 2019 and also found in South Sumatera. S. frugiperda has attacked a lot of host plant species. A record of the fall armyworm host plant species is required to comprehend pest's biology and ecology. The purpose of this study was to identify the host plant species of S. frugiperda. The surveys to collect and to record the host plants have been conducted in South Sumatra consisted of seven districts/cities of Ogan Ilir, Palembang, Lahat, Pagar Alam, Prabumulih, Muara Enim, and Banyuasin. This study has found 28 species of S. frugiperda host plants, such as Zea mays, Elaeis guineensis, Oryza sativa, Lactuca sativa, Brassica oleracea, Amaranthus hybridus, Cucumis sativus, Manihot esculenta, Vigna unguiculata, Arachis hypogaea, Persea americana, Fragaria ananassa, Rosa sp., Ipomoea aquatic, Ipomoea batatas, Solanum melongena. S. frugiperda host plants recorded were 14 plant families, specifically Areceae, Cyperaceae, Poaceae, Musaceae, Asteraceae, Brassicaceae, Amaranthaceae, Cucurbitaceae, Euphorbiaceae, Fabaceae, Lauraceae, Rosaceae, Convolvulaceae, and Solanaceae. There were 13 species of monocot plants and 15 species of dicot plants that can be eaten by S. frugiperda. So, the S. frugiperda has lots of host plant species including monocotyledonous and dicotyledonous plants.